Silicon carbide fiber reinforced ceramic-based composite material as well as preparation method and application thereof

By introducing ceramic particles and boron carbide into the matrix of silicon carbide fiber-reinforced silicon carbide ceramic composite material, the modulus matching and thermal expansion coefficient matching are optimized, the problem of the composite material being prone to crack defects under high temperature and water vapor conditions is solved, and efficient mechanical properties and water-oxygen corrosion resistance are achieved.

CN119874377AActive Publication Date: 2025-04-25NINGBO INST OF NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202510352616.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-25
Estimated Expiration
2045-03-25

Smart Images

  • Figure CN119874377A_ABST
    Figure CN119874377A_ABST
Patent Text Reader

Abstract

The invention provides a silicon carbide fiber reinforced ceramic-based composite material as well as a preparation method and application thereof, and belongs to the technical field of ceramic-based composite materials. The composite material comprises a silicon carbide fiber reinforced phase, a boron nitride interface layer and a silicon-based multiphase ceramic matrix from inside to outside, the silicon-based multiphase ceramic matrix comprises an infiltration reaction generation phase, an introduced ceramic particle phase and a silicon-containing binary alloy phase, and the infiltration reaction generation phase comprises a water-oxygen corrosion resistant phase, a silicon phase, a silicon carbide phase and a boride phase. The water oxygen corrosion resistant phase comprises a compound of boron and any element of yttrium, ytterbium, hafnium, molybdenum and aluminum, the boride phase comprises B12 (C, Si, B) 3, the bending strength of the composite material is larger than or equal to 600 MPa, and the fracture toughness of the composite material is larger than or equal to 19 MPa.m < 1 / 2 >. According to the preparation method, the matching property among the components of the composite material is optimized, the mechanical property of the composite material is improved, and a new thought and a process method are provided for preparing the high-strength and water-oxygen-corrosion-resistant ceramic matrix composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic matrix composite materials, and in particular to a silicon carbide fiber reinforced ceramic matrix composite material and a preparation method and application thereof. Background Art

[0002] Silicon carbide fiber reinforced silicon carbide ceramic matrix (SiC f / SiC) composite materials not only inherit the advantages of silicon carbide ceramic materials such as high temperature resistance, wear resistance, corrosion resistance and creep resistance, but also make up for the defects of insufficient toughness and poor resistance to external impact loads of ceramic materials through the strengthening and toughening mechanism of silicon carbide fibers, and have excellent comprehensive performance. f / SiC) composite materials are widely used in aerospace engines and other fields. The working environment of aerospace engines is extremely harsh. They need to operate under high temperature, complex stress, water vapor corrosion, sand erosion and other conditions, and have a long service life. However, under high temperature and water vapor conditions, SiC will react with water vapor to generate SiO(OH) 2 and Si(OH) 4 The commonly used BN interface will also react with water vapor to generate volatile H 3 BO 3 These reactions can cause the composite material to fail quickly and fail to meet the requirements for long-life use.

[0003] In order to improve the water-oxygen corrosion resistance of silicon carbide fiber reinforced silicon carbide ceramic matrix composites, the SiC matrix is ​​often modified. Reference 1 "Li Jingxin, Liu Yongsheng, He Fang, et al. Preparation and properties of SiC / SiC-SiYC with excellent water-oxygen corrosion resistance[J]. Journal of the European Ceramic Society, 2023, 43(14): 6606-6611." Li et al. used RMI to introduce carbon source and silicon-yttrium (Si-Y) alloy into the SiC matrix to prepare SiC f / SiC-SiYC composite material. The porosity of this material is only 2.0%. After water-oxygen corrosion, the dense oxide layer formed on the surface effectively protects the composite material, indicating that the SiC f Introducing Si-Y alloy into SiC can construct a matrix that is resistant to water and oxygen corrosion. Chinese patent ZL202210239625.8 adopts a method of vacuum impregnation combined with reactive melt infiltration, using Si-Y alloy and B 4C to generate Si-YBC quaternary matrix and obtain SiC f / Si-YBC composite material effectively improves the water and oxygen corrosion resistance of silicon carbide fiber reinforced silicon carbide ceramic matrix composite materials.

[0004] Although introducing Si-Y alloy into SiC matrix to make it react under water-oxygen corrosion conditions to generate water-oxygen corrosion resistant phase and self-healing phase is an effective method to improve the water-oxygen corrosion resistance of silicon carbide fiber reinforced silicon carbide ceramic matrix composites, the presence of cracks inside Si-YC and Si-YBC matrices significantly reduces the high-temperature mechanical properties of the composites, thereby affecting the service life of aircraft engines. Therefore, how to improve the water-oxygen corrosion resistance of silicon carbide fiber reinforced silicon carbide ceramic matrix composites while solving the crack defects caused by residual thermal stress inside the composite materials, so that it has both excellent mechanical properties and water-oxygen corrosion resistance, is an urgent problem to be solved. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a silicon carbide fiber reinforced ceramic matrix composite material and a preparation method and application thereof. The silicon carbide fiber reinforced ceramic matrix composite material improves the modulus matching between the components of the composite material so that it has both excellent mechanical properties and water-oxygen corrosion resistance.

[0006] The specific technical scheme of the present invention is: In the first aspect, the present invention provides a silicon carbide fiber reinforced ceramic matrix composite material, comprising a silicon carbide fiber reinforcement phase, a boron nitride interface layer and a silicon-based multiphase ceramic matrix from the inside to the outside, wherein the phase composition of the silicon-based multiphase ceramic matrix comprises a phase generated by a melt infiltration reaction, an introduced ceramic particle phase and a silicon-containing binary alloy phase, wherein the alloy element in the silicon-containing binary alloy is any one of yttrium, ytterbium, hafnium, molybdenum and aluminum, wherein the phase generated by the melt infiltration reaction comprises a water-oxygen corrosion-resistant phase, a silicon phase, a silicon carbide phase and a boride phase, wherein the water-oxygen corrosion-resistant phase comprises a compound of boron and any one of yttrium, ytterbium, hafnium, molybdenum and aluminum, and the boride phase comprises B 12 (C,Si,B) 3 The particle size of the ceramic particles in the ceramic particle phase is 0.1-10 μm, and the flexural strength of the silicon carbide fiber reinforced ceramic matrix composite material is ≥600 MPa and the fracture toughness is ≥19 MPa·m 1 / 2 .

[0007] The present invention analyzes the reasons for the decline in mechanical properties of silicon carbide fiber reinforced ceramic matrix composites when they serve for a long time in a high-temperature environment. The modulus mismatch and thermal expansion mismatch between the components of the silicon carbide fiber reinforced ceramic matrix composites under high-temperature conditions lead to the accumulation of residual thermal stress inside the silicon carbide fiber reinforced ceramic matrix composites and the generation of cracks, which ultimately causes a significant decline in the mechanical properties of the silicon carbide fiber reinforced ceramic matrix composites, thereby affecting the service life of aircraft engines. Based on the above analysis, the silicon carbide fiber reinforced ceramic matrix composite material provided by the present invention optimizes the modulus matching and thermal expansion coefficient matching between the silicon-based multiphase ceramic matrix and the silicon carbide fiber reinforced phase and the boron nitride interface layer in the composite material by introducing ceramic particles with a particle size of 0.1-10 μm into the matrix of the composite material. At the same time, the addition of ceramic particles also optimizes the modulus matching and thermal expansion coefficient matching between the various phases inside the silicon-based multiphase ceramic matrix, and significantly improves the flexural strength and fracture toughness of the composite material; the water-oxygen corrosion-resistant phase in the phase generated by the infiltration reaction has excellent water-oxygen corrosion resistance, ensuring the water-oxygen corrosion resistance of the silicon carbide fiber reinforced ceramic matrix composite material; under the mutual cooperation of the silicon-based multiphase ceramic matrix, the boron nitride interface layer and the silicon carbide fiber reinforced phase, the silicon carbide fiber reinforced ceramic matrix composite material has both excellent mechanical properties and water-oxygen corrosion resistance.

[0008] In a possible implementation, the ceramic particles are selected from at least one of carbide ceramic particles, nitride ceramic particles and boride ceramic particles.

[0009] Furthermore, the ceramic particles are selected from at least one of silicon carbide ceramic particles, silicon nitride ceramic particles, zirconium carbide ceramic particles, zirconium nitride ceramic particles and zirconium boride ceramic particles.

[0010] Silicon carbide ceramic particles, silicon nitride ceramic particles, zirconium carbide ceramic particles, zirconium nitride ceramic particles and zirconium boride ceramic particles have an elastic modulus greater than or equal to that of silicon carbide, are resistant to high temperatures, and do not react with the infiltration material.

[0011] In a possible implementation, the silicon carbide fiber reinforced ceramic matrix composite material has a flexural strength of ≥700 MPa and a fracture toughness of ≥20 MPa·m 1 / 2 By further optimizing the content of ceramic particles introduced into silicon carbide fiber reinforced ceramic matrix composites, the flexural strength of silicon carbide fiber reinforced ceramic matrix composites is ≥700 MPa and the fracture toughness is ≥20 MPa·m 1 / 2 , which can better meet the requirements of mechanical properties of silicon carbide fiber reinforced ceramic matrix composites in the fields of aviation engines, industrial gas turbines or aerospace engines.

[0012] In a second aspect, the present invention provides a method for preparing a silicon carbide fiber reinforced ceramic matrix composite material, comprising the following steps: S1. Depositing a boron nitride interface layer on a silicon carbide fiber preform by a chemical vapor infiltration process to obtain a silicon carbide fiber composite preform; S2, using vacuum impregnation and pressure impregnation to impregnate the multiphase ceramic slurry into the silicon carbide fiber composite preform obtained in step S1, repeating the vacuum impregnation and pressure impregnation until the weight of the silicon carbide fiber composite preform increases by 12-15wt.%, to obtain a composite material preform; the multiphase ceramic slurry contains 0.5-1% by weight of sodium carboxymethyl cellulose, 20-50% of boron carbide, 10-30% of ceramic particles and the balance of deionized water, and the particle size of the ceramic particles is 0.1-10 μm; S3, the composite material preform described in step S2 is subjected to reactive melt infiltration in the infiltration material to obtain a silicon carbide fiber reinforced ceramic matrix composite material.

[0013] The method for preparing a silicon carbide fiber reinforced ceramic matrix composite material provided by the present invention introduces ceramic particles with a particle size of 0.1-10 μm and boron carbide powder into a matrix of the composite material, and controls the relative contents of ceramic particles, sodium carboxymethyl cellulose and boron carbide in a multiphase ceramic slurry used for impregnation treatment and the number of impregnations to control the amount of ceramic particles and boron carbide impregnated into the silicon carbide fiber reinforced ceramic matrix composite material through impregnation treatment, thereby optimizing the elastic modulus matching and thermal expansion coefficient matching between the components of the composite material, significantly improving the flexural strength and fracture toughness of the silicon carbide fiber reinforced ceramic matrix composite material, and at the same time, the boron carbide in the matrix reacts with the infiltration material to generate a water-oxygen corrosion-resistant phase, so that the prepared silicon carbide fiber reinforced ceramic matrix composite material has both excellent mechanical properties and water-oxygen corrosion resistance.

[0014] In a possible implementation, the silicon carbide fiber preform in step S1 is formed by laminating silicon carbide fiber cloth or by weaving silicon carbide fibers. The two-dimensional laminated silicon carbide fiber preform obtained by stacking silicon carbide fiber cloth at a certain laying angle has high in-plane mechanical properties and is suitable for preparing thin-walled components; the use of a woven structure preform allows the composite material to meet different mechanical property requirements, and has low manufacturing costs and a short production cycle.

[0015] In a possible implementation, the deposition conditions of the boron nitride interface layer in step S1 are boron chloride as a boron source, ammonia as a nitrogen source, a deposition temperature of 600-800 °C, and a pressure of 5-10 kPa. The use of the above-mentioned deposition gas source and temperature of the boron nitride interface layer is conducive to obtaining a boron nitride with a uniform composition of the interface layer and a stoichiometric ratio close to 1:1; the use of a low gas pressure of 5-10 kPa is conducive to enhancing the diffusion capacity of the deposition gas source between the fiber bundles, which is particularly suitable for silicon carbide fiber preforms formed by complex weaving or laminated fibers, ensuring that the thickness of the deposited boron nitride interface layer is uniform.

[0016] In a possible implementation, the thickness of the boron nitride interface layer is 500-1000 nm. The use of a boron nitride interface layer with a thickness of 500-1000 nm can not only prevent the reaction diffusion between the silicon carbide fiber and the matrix, but also protect the silicon carbide fiber from erosion by external corrosive atmospheres such as water vapor, and can also maintain the weak interface bonding between the silicon carbide fiber and the matrix, while giving full play to the bearing capacity of the silicon carbide fiber, while improving the toughness of the silicon carbide fiber reinforced ceramic matrix composite material.

[0017] In a possible embodiment, the process of vacuum impregnation and pressure impregnation in step S2 is to first place the silicon carbide fiber preform obtained in step S1 in a vacuum dish, evacuate the vacuum dish to a pressure of ≤-0.09 MPa, and maintain it for 20-30 min, and then immerse the silicon carbide fiber preform in the composite ceramic slurry and maintain it for 20-40 min; then, place the composite ceramic slurry together with the silicon carbide fiber preform in a closed container, pressurize it to 0.6-2.0 MPa, maintain it for 20-120 min, and then take it out. The vacuum impregnation combined with the pressure impregnation process is used to first fully extract the gas in the silicon carbide fiber preform through a vacuum environment of ≤-0.09 MPa to avoid the occurrence of gas blockage during the subsequent impregnation process and ensure that the slurry impregnation path is unobstructed; the vacuum impregnation time of 20-40 minutes and the pressure impregnation time of 20-120 minutes allow the slurry to fully penetrate into the silicon carbide fiber preform under the pressure gradient, so that the slurry can fill the micron-level pores; at the same time, it also avoids insufficient impregnation and uneven impregnation due to too short a time, resulting in a large number of unfilled pores in the composite material. The use of a high pressure of 0.6-2.0 MPa for pressure impregnation can generate a significant pressure gradient to drive the slurry to quickly penetrate into the silicon carbide fiber preform, significantly reducing the unfilled pores.

[0018] In a possible implementation, the particle size of the boron carbide in step S2 is 0.1-10 μm. Boron carbide powder with a particle size of 0.1-10 μm can be evenly filled into the silicon carbide fiber preform, which is conducive to sufficient reaction with the infiltration material later.

[0019] In a possible embodiment, the configuration process of the composite ceramic slurry in step S2 is to first dissolve the sodium carboxymethyl cellulose in deionized water at a temperature of 60-80 ° C, stir evenly to obtain a dispersed solution; then add the boron carbide and the ceramic particles to the dispersed solution to obtain a mixed slurry; the mixed slurry is ball-milled to obtain a uniformly dispersed composite ceramic slurry. Dissolve sodium carboxymethyl cellulose in deionized water at 60-80 ° C. High temperature can accelerate the extension of its molecular chain and improve the dispersion efficiency. In the range of 60-80 ° C, it can avoid high-temperature degradation of sodium carboxymethyl cellulose, ensure that it is fully dissolved to form a stable colloid, and provide a uniform medium for subsequent particle dispersion; first prepare a sodium carboxymethyl cellulose dispersion and then add boron carbide and ceramic particles step by step. The electrostatic repulsion and steric hindrance effect of sodium carboxymethyl cellulose can wrap the particle surface layer by layer, inhibiting the sedimentation or agglomeration of particles due to density differences; the mechanical shear force during ball milling can break the soft agglomerates of particles, so that boron carbide and ceramic particles can be dispersed at the submicron or even nanometer level.

[0020] Furthermore, the ball mill has a rotation speed of 200-300 r / min, a time of 24-36 h, and a corundum ball size of 10-30 mm. The medium rotation speed range (200-300 r / min) can provide sufficient mechanical shear force to break particles, and can also avoid excessive heating and increased energy consumption caused by high rotation speed (such as >1000 r / min). The 200-300 r / min range is suitable for processing hard material boron carbide and ceramic particles, reducing the wear of grinding balls and equipment and extending their service life; the long-term ball milling of 24-36 h can fully break the soft agglomerates of particles, so that boron carbide or ceramic particles can be dispersed at the submicron to nanometer level; compared with large-sized grinding balls, corundum balls with a size of 10-30 mm have more contact points per unit volume, which can improve grinding efficiency and shorten the time to reach the target particle size.

[0021] In a possible implementation, the infiltration material in step S3 is selected from one of silicon-yttrium alloy, silicon-ytterbium alloy, silicon-hafnium alloy, silicon-molybdenum alloy and silicon-aluminum alloy. After entering the matrix of the composite material, silicon-yttrium alloy, silicon-ytterbium alloy, silicon-hafnium alloy, silicon-molybdenum alloy and silicon-aluminum alloy can react with boron carbide to generate a water-oxygen corrosion-resistant phase.

[0022] In a possible implementation, the insulation temperature of the reaction solution infiltration in step S3 is 1200-1500°C and the insulation time is 30-90 min. In the high temperature range of 1200-1500°C, the filling of the pores in the composite material preform by the infiltration material can be effectively promoted. Combined with the insulation time of 30-90 min, it can ensure the full progress of the infiltration reaction and avoid the damage to the silicon carbide fiber caused by long-term high temperature.

[0023] In a third aspect, the present invention also provides applications of the silicon carbide fiber reinforced ceramic matrix composite material in the fields of aircraft engines, industrial gas turbines or aerospace engines.

[0024] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0025] The reagents and raw materials used in the present invention are commercially available.

[0026] The positive and progressive effects of the present invention are: The silicon carbide fiber reinforced ceramic matrix composite material provided by the present invention has both excellent mechanical properties and water-oxygen corrosion resistance. The water-oxygen corrosion resistance phase in the silicon-based multiphase ceramic matrix can ensure that the silicon carbide fiber reinforced ceramic matrix composite material has excellent water corrosion resistance. The ceramic particles in the silicon-based multiphase ceramic matrix make the modulus matching and thermal expansion coefficient matching between the silicon carbide fiber reinforced phase and the boron nitride interface layer in the silicon carbide fiber reinforced ceramic matrix composite material. At the same time, the addition of ceramic particles also optimizes the modulus matching and thermal expansion coefficient matching between the various phases inside the silicon-based multiphase ceramic matrix. The expansion coefficients are matched, and the flexural strength and fracture toughness of the composite material are significantly improved under the mutual cooperation of the silicon-based multiphase ceramic matrix, the boron nitride interface layer and the silicon carbide fiber reinforcement phase; the water-oxygen corrosion-resistant phase in the phase generated by the infiltration reaction has excellent water-oxygen corrosion resistance, ensuring the water-oxygen corrosion resistance of the silicon carbide fiber-reinforced ceramic-based composite material; under the mutual cooperation of the silicon-based multiphase ceramic matrix, the boron nitride interface layer and the silicon carbide fiber reinforcement phase, the silicon carbide fiber-reinforced ceramic-based composite material has both excellent mechanical properties and water-oxygen corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the XRD pattern of the silicon carbide particle-modified silicon carbide fiber-reinforced ceramic matrix composite material prepared in Example 1.

[0028] Figure 2 This is a cross-sectional SEM image of the silicon carbide particle-modified silicon carbide fiber-reinforced ceramic matrix composite material prepared in Example 1.

[0029] Figure 3 The graph is a data diagram of the flexural strength of the composite materials prepared in Examples 1-6 and the comparative example.

[0030] Figure 4 Fracture toughness data of the composite materials prepared in Examples 1-4. DETAILED DESCRIPTION

[0031] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0032] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0033] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.

[0034] Example 1

[0035] This embodiment provides a silicon carbide particle-modified silicon carbide fiber-reinforced ceramic matrix composite material, which is prepared by the following method: S1. A boron nitride interface with a thickness of 600 nm was deposited on a two-dimensional laminated silicon carbide fiber preform using a chemical vapor infiltration process (CVI). The chemical vapor infiltration process used boron chloride as a boron source and ammonia as a nitrogen source. The deposition temperature was 650 °C and the pressure was 5 kPa. S2. Dissolve sodium carboxymethyl cellulose in deionized water, heat to 80 °C in a water bath and stir magnetically until the sodium carboxymethyl cellulose is uniformly dispersed to obtain a dispersed solution; after the dispersed solution is cooled, add boron carbide powder and silicon carbide particles to obtain a mixed slurry, the mixed slurry contains 30 wt.% boron carbide powder, 10 wt.% silicon carbide particles and 1.0 wt.% sodium carboxymethyl cellulose, the particle size of the boron carbide powder is about 1-3 μm, and the particle size of the silicon carbide particles is about 5 μm; pour the mixed slurry into a ball mill filled with corundum balls with a diameter of 10-30 mm, wet ball mill for 24 h, and the ball mill speed is 300 r / min to obtain a uniformly dispersed mixed slurry; S3, firstly, vacuum impregnation is performed, the silicon carbide fiber preform obtained in step S1 is placed in a vacuum dish, and the vacuum is evacuated until the air pressure in the vacuum dish is lower than -0.09 MPa, and the vacuum dish is maintained for 30 min; then, the silicon carbide fiber preform is immersed in the mixed slurry of step S2, and the maintenance time is 30 min; then, pressure impregnation is performed, the slurry together with the silicon carbide fiber preform is placed in a closed container and pressurized to 0.8 MPa, and the slurry is maintained for 60 min before being taken out, the surface of the silicon carbide fiber preform is wiped dry, and then dried at 70 ° C, and the vacuum impregnation and pressure impregnation processes are repeated for 5 rounds until the weight gain of the silicon carbide fiber preform reaches 12-15 wt.%, so as to obtain a composite material preform; S4. The composite material preform obtained in step S3 is embedded with silicon-yttrium alloy, placed in a graphite crucible, and sent to a vacuum infiltration furnace for reaction melt infiltration. The insulation temperature is 1400° C. and the insulation time is 60 min to obtain a silicon carbide particle-modified silicon carbide fiber-reinforced ceramic matrix composite material.

[0036] Example 2

[0037] This embodiment provides a silicon carbide particle-modified silicon carbide fiber-reinforced ceramic matrix composite material, which is prepared by the following method: S1. A boron nitride interface with a thickness of 600 nm was deposited on a two-dimensional laminated silicon carbide fiber preform using a chemical vapor infiltration process (CVI). The chemical vapor infiltration process used boron chloride as a boron source and ammonia as a nitrogen source. The deposition temperature was 650 °C and the pressure was 5 kPa. S2. Dissolve sodium carboxymethyl cellulose in deionized water, heat to 80 °C in a water bath and stir magnetically until the sodium carboxymethyl cellulose is uniformly dispersed to obtain a dispersed solution; after the dispersed solution is cooled, add boron carbide powder and silicon carbide particles to obtain a mixed slurry, the mixed slurry contains 35 wt.% boron carbide powder, 10 wt.% silicon carbide particles and 1.0 wt.% sodium carboxymethyl cellulose, the particle size of the boron carbide powder is about 1-3 μm, and the particle size of the silicon carbide particles is about 5 μm; pour the mixed slurry into a ball mill filled with corundum balls with a diameter of 10-30 mm, wet ball mill for 24 h, and the ball mill speed is 300 r / min to obtain a uniformly dispersed mixed slurry; S3, firstly, vacuum impregnation is performed, the silicon carbide fiber preform obtained in step S1 is placed in a vacuum dish, and the vacuum is evacuated until the air pressure in the vacuum dish is lower than -0.09 MPa, and the vacuum dish is maintained for 30 min; then, the silicon carbide fiber preform is immersed in the mixed slurry of step S2, and the maintenance time is 30 min; then, pressure impregnation is performed, the slurry together with the silicon carbide fiber preform is placed in a closed container and pressurized to 0.8 MPa, and the slurry is maintained for 60 min before being taken out, the surface of the silicon carbide fiber preform is wiped dry, and then dried at 70 ° C, and the vacuum impregnation and pressure impregnation processes are repeated for 5 rounds until the weight gain of the silicon carbide fiber preform reaches 12-15 wt.%, so as to obtain a composite material preform; S4. The composite material preform obtained in step 3 is embedded with silicon-yttrium alloy, placed in a graphite crucible, and sent to a vacuum infiltration furnace for reaction melt infiltration. The insulation temperature is 1400°C and the insulation time is 60 min to obtain a silicon carbide particle-modified silicon carbide fiber-reinforced ceramic matrix composite material.

[0038] Example 3

[0039] This embodiment provides a silicon carbide particle-modified silicon carbide fiber-reinforced ceramic matrix composite material, which is prepared by the following method: S1. A boron nitride interface with a thickness of 600 nm was deposited on a two-dimensional laminated silicon carbide fiber preform using a chemical vapor infiltration process (CVI). The chemical vapor infiltration process used boron chloride as a boron source and ammonia as a nitrogen source. The deposition temperature was 650 °C and the pressure was 5 kPa. S2. Dissolve sodium carboxymethyl cellulose in deionized water, heat to 80 °C in a water bath and stir magnetically until the sodium carboxymethyl cellulose is uniformly dispersed to obtain a dispersed solution; after the dispersed solution is cooled, add boron carbide powder and silicon carbide particles to obtain a mixed slurry, the mixed slurry contains 40 wt.% boron carbide powder, 10 wt.% silicon carbide particles and 1.0 wt.% sodium carboxymethyl cellulose, the particle size of the boron carbide powder is about 1-3 μm, and the particle size of the silicon carbide particles is about 5 μm; pour the mixed slurry into a ball mill filled with corundum balls with a diameter of 10-30 mm, wet ball mill for 24 h, and the ball mill speed is 300 r / min to obtain a uniformly dispersed mixed slurry; S3, firstly, vacuum impregnation is performed, the silicon carbide fiber preform obtained in step S1 is placed in a vacuum dish, and the vacuum is evacuated until the air pressure in the vacuum dish is lower than -0.09 MPa, and the vacuum dish is maintained for 30 min; then, the silicon carbide fiber preform is immersed in the mixed slurry of step S2, and the maintenance time is 30 min; then, pressure impregnation is performed, the slurry together with the silicon carbide fiber preform is placed in a closed container and pressurized to 0.8 MPa, and the slurry is maintained for 60 min before being taken out, the surface of the silicon carbide fiber preform is wiped dry, and then dried at 70 ° C, and the vacuum impregnation and pressure impregnation processes are repeated for 5 rounds until the weight gain of the silicon carbide fiber preform reaches 12-15 wt.%, so as to obtain a composite material preform; S4. The composite material preform obtained in step S3 is embedded with silicon-yttrium alloy, placed in a graphite crucible, and sent to a vacuum infiltration furnace for reaction melt infiltration. The insulation temperature is 1400° C. and the insulation time is 60 min to obtain a silicon carbide particle-modified silicon carbide fiber-reinforced ceramic matrix composite material.

[0040] Example 4

[0041] This embodiment provides a silicon carbide particle-modified silicon carbide fiber-reinforced ceramic matrix composite material, which is prepared by the following method: S1. A boron nitride interface with a thickness of 600 nm was deposited on a two-dimensional laminated silicon carbide fiber preform using a chemical vapor infiltration process (CVI). The chemical vapor infiltration process used boron chloride as a boron source and ammonia as a nitrogen source. The deposition temperature was 650 °C and the pressure was 5 kPa. S2. Dissolve sodium carboxymethyl cellulose in deionized water, heat to 80 °C in a water bath and stir magnetically until the sodium carboxymethyl cellulose is uniformly dispersed to obtain a dispersed solution; after the dispersed solution is cooled, add boron carbide powder and silicon carbide particles to obtain a mixed slurry, the mixed slurry contains 30 wt.% boron carbide powder, 15 wt.% silicon carbide particles and 1.0 wt.% sodium carboxymethyl cellulose, the particle size of the boron carbide powder is about 1-3 μm, and the particle size of the silicon carbide particles is about 5 μm; pour the mixed slurry into a ball mill filled with corundum balls with a diameter of 10-30 mm, wet ball mill for 24 h, and the ball mill speed is 300 r / min to obtain a uniformly dispersed mixed slurry; S3, firstly, vacuum impregnation is performed, the silicon carbide fiber preform obtained in step S1 is placed in a vacuum dish, and the vacuum is evacuated until the air pressure in the vacuum dish is lower than -0.09 MPa, and the vacuum dish is maintained for 30 min; then, the silicon carbide fiber preform is immersed in the mixed slurry of step S2, and the maintenance time is 30 min; then, pressure impregnation is performed, the slurry together with the silicon carbide fiber preform is placed in a closed container and pressurized to 0.8 MPa, and the slurry is maintained for 60 min before being taken out, the surface of the silicon carbide fiber preform is wiped dry, and then dried at 70 ° C, and the vacuum impregnation and pressure impregnation processes are repeated for 5 rounds until the weight gain of the silicon carbide fiber preform reaches 12-15 wt.%, so as to obtain a composite material preform; S4. The composite material preform obtained in step S3 is embedded with silicon-yttrium alloy, placed in a graphite crucible, and sent to a vacuum infiltration furnace for reaction melt infiltration. The insulation temperature is 1400° C. and the insulation time is 60 min to obtain a silicon carbide particle-modified silicon carbide fiber-reinforced ceramic matrix composite material.

[0042] Example 5

[0043] This embodiment provides a silicon nitride particle modified silicon carbide fiber reinforced ceramic matrix composite material, which is prepared by the following method: S1. A boron nitride interface with a thickness of 600 nm was deposited on a two-dimensional laminated silicon carbide fiber preform using a chemical vapor infiltration process (CVI). The chemical vapor infiltration process used boron chloride as a boron source and ammonia as a nitrogen source. The deposition temperature was 650 °C and the pressure was 5 kPa. S2. Dissolve sodium carboxymethyl cellulose in deionized water, heat to 80 °C in a water bath and stir magnetically until the sodium carboxymethyl cellulose is uniformly dispersed to obtain a dispersed solution; after the dispersed solution is cooled, add boron carbide powder and silicon nitride particles to obtain a mixed slurry, the mixed slurry contains 30 wt.% boron carbide powder, 10 wt.% silicon nitride particles and 1.0 wt.% sodium carboxymethyl cellulose, the particle size of the boron carbide powder is about 1-3 μm, and the particle size of the silicon nitride particles is about 1-3 μm; pour the mixed slurry into a ball mill filled with corundum balls with a diameter of 10-30 mm, wet ball mill for 24 h, and the ball mill speed is 300 r / min to obtain a uniformly dispersed mixed slurry; S3, firstly, vacuum impregnation is performed, the silicon carbide fiber preform obtained in step S1 is placed in a vacuum dish, and the vacuum is evacuated until the air pressure in the vacuum dish is lower than -0.09 MPa, and the vacuum dish is maintained for 30 min; then, the silicon carbide fiber preform is immersed in the mixed slurry of step S2, and the maintenance time is 30 min; then, pressure impregnation is performed, the slurry together with the silicon carbide fiber preform is placed in a closed container and pressurized to 0.8 MPa, and the slurry is maintained for 60 min before being taken out, the surface of the silicon carbide fiber preform is wiped dry, and then dried at 70 ° C, and the vacuum impregnation and pressure impregnation processes are repeated for 5 rounds until the weight gain of the silicon carbide fiber preform reaches 12-15 wt.%, so as to obtain a composite material preform; S4. The composite material preform obtained in step S3 is embedded with silicon-yttrium alloy, placed in a graphite crucible, and sent to a vacuum infiltration furnace for reaction melt infiltration. The insulation temperature is 1400° C. and the insulation time is 60 min to obtain a silicon nitride particle-modified silicon carbide fiber-reinforced ceramic matrix composite material.

[0044] Example 6

[0045] This embodiment provides a zirconium carbide particle modified silicon carbide fiber reinforced ceramic matrix composite material, which is prepared by the following method: S1. A boron nitride interface with a thickness of 600 nm was deposited on a two-dimensional laminated silicon carbide fiber preform using a chemical vapor infiltration process (CVI). The chemical vapor infiltration process used boron chloride as a boron source and ammonia as a nitrogen source. The deposition temperature was 650 °C and the pressure was 5 kPa. S2. Dissolve sodium carboxymethyl cellulose in deionized water, heat to 80 °C in a water bath and stir magnetically until the sodium carboxymethyl cellulose is uniformly dispersed to obtain a dispersed solution; after the dispersed solution is cooled, add boron carbide powder and zirconium carbide particles to obtain a mixed slurry, the mixed slurry contains 30 wt.% boron carbide powder, 20 wt.% zirconium carbide particles and 1.0 wt.% sodium carboxymethyl cellulose, the particle size of the boron carbide powder is about 1-3 μm, and the particle size of the zirconium carbide particles is about 2-5 μm; pour the mixed slurry into a ball mill filled with corundum balls with a diameter of 10-30 mm, wet ball mill for 24 h, and the ball mill speed is 300 r / min to obtain a uniformly dispersed mixed slurry; S3, firstly, vacuum impregnation is performed, the silicon carbide fiber preform obtained in step S1 is placed in a vacuum dish, and the vacuum is evacuated until the air pressure in the vacuum dish is lower than -0.09 MPa, and the vacuum dish is maintained for 30 min; then, the silicon carbide fiber preform is immersed in the mixed slurry of step S2, and the maintenance time is 30 min; then, pressure impregnation is performed, the slurry together with the silicon carbide fiber preform is placed in a closed container and pressurized to 0.8 MPa, and the slurry is maintained for 60 min before being taken out, the surface of the silicon carbide fiber preform is wiped dry, and then dried at 70 ° C, and the vacuum impregnation and pressure impregnation processes are repeated for 5 rounds until the weight gain of the silicon carbide fiber preform reaches 12-15 wt.%, so as to obtain a composite material preform; S4. The composite material preform obtained in step S3 is embedded with silicon-yttrium alloy, placed in a graphite crucible, and sent to a vacuum infiltration furnace for reaction melt infiltration. The insulation temperature is 1400° C. and the insulation time is 60 min to obtain a zirconium carbide particle-modified silicon carbide fiber-reinforced ceramic matrix composite material.

[0046] Comparative Example 1 This comparative example provides a SiC f / Si-YBC composite material, which is prepared by the following method: S1. A 600 nm thick boron nitride interface was deposited on a two-dimensional laminated silicon carbide fiber preform using chemical vapor infiltration (CVI). Boron chloride was used as the boron source and ammonia was used as the nitrogen source. The deposition temperature was 650 °C and the pressure was 5 kPa. Then, a certain amount of silicon carbide substrate was deposited using the CVI process. Trichloromethylsilane (CH 3 SiCl 3 , referred to as MTS) as the gas source, Ar as the dilution gas, high-purity hydrogen as the carrier gas of trichloromethylsilane, the deposition temperature is 1000 ℃, the pressure is 5 kPa, and the density of the prepared 3 Porous SiC f / SiC preform; S2. Dissolve sodium carboxymethyl cellulose in deionized water, heat to 80°C in a water bath and stir magnetically until the sodium carboxymethyl cellulose is uniformly dispersed to obtain a dispersed solution; after the dispersed solution is cooled, add boron carbide powder to obtain a boron carbide slurry, wherein the boron carbide slurry contains 30 wt.% boron carbide powder and 1.0 wt.% sodium carboxymethyl cellulose; pour the boron carbide slurry into a ball mill equipped with a corundum ball with a diameter of 10-30 mm, and wet-mill for 24 h at a ball mill speed of 200 r / min to obtain a uniformly dispersed boron carbide slurry; S3, the porous SiC fThe preform of porous SiC was placed in a vacuum vessel and evacuated until the pressure inside the vacuum vessel was lower than -0.09 MPa and maintained for 30 min. f The preform is immersed in the boron carbide slurry of step S2 for 30 min; and then pressure impregnation is performed to mix the slurry with the porous SiC f The / SiC preform was placed in a sealed container and pressurized to 0.8 MPa. After holding for 30 min, it was taken out and the porous SiC f The surface of the SiC preform is wiped dry and dried, and the vacuum impregnation and pressure impregnation processes are repeated for 5 rounds until the weight gain of the composite body reaches 10-13 wt.%, thereby obtaining a composite preform; S4, using the embedding method, placing the composite material preform obtained in step S3 and the Si-Y alloy powder in a graphite crucible, and sending them into a vacuum infiltration furnace for reaction melt infiltration, with the holding temperature being 1350°C and the holding time being 60 min, to obtain SiC f / Si-YBC composite materials.

[0047] The composite materials prepared in Examples 1-6 and Comparative Example 1 were characterized and tested, and the results were as follows: Figure 1 The XRD pattern of the silicon carbide fiber-reinforced ceramic matrix composite material modified by silicon carbide particles prepared in Example 1. As can be seen from the figure, the composite material is mainly composed of SiC, Si, YSi 2 and YB 4 Composition, of which YB 4 By YSi 2 and B 4 C reaction; SiC includes SiC ceramic particles introduced by slurry impregnation and SiC generated by melt infiltration reaction, YSi 2 The Si is the residue after the infiltration reaction, and includes the Si remaining in the Si-Y alloy after the infiltration reaction and the Si phase generated by the infiltration reaction.

[0048] Figure 2 This is a SEM image of the cross section of the silicon carbide particle-modified silicon carbide fiber-reinforced ceramic matrix composite material prepared in Example 1. Figure 2 (a) and Figure 2 (b) SEM images of two different regions of the composite material. In the matrix of the composite material, each phase is evenly distributed. Figure 2 The dark gray area in (a) is the silicon carbide ceramic particle phase (SI SiC), and the light gray area is the Si phase generated by the infiltration reaction. It can be seen that in this area, the SiC particles introduced by slurry impregnation are dispersed in the Si phase. Figure 2 The dark gray area in (b) is the SiC ceramic particle phase (SI SiC) introduced by slurry impregnation, and the bright white area is YSi 2Phase (YSi 2 ), the light grey area is the SiC phase generated by the infiltration reaction (RMI SiC), YB 4 Mixed in the RMI SiC phase, the black area is the B generated by the reaction 12 (C,Si,B) 3 phase, it can be seen that the B generated by the reaction in this area 12 (C,Si,B) 3 phase, SiC particles introduced by slurry impregnation, residual YSi 2 phase is embedded in the SiC phase generated by the RMI reaction.

[0049] Figure 3 The flexural strength data of the composite materials prepared in Examples 1-6 and Comparative Example 1 are shown in FIG. As can be seen from the figure, the flexural strength of the ceramic particle modified silicon carbide fiber reinforced ceramic matrix composite materials prepared in Examples 1-6 is significantly higher than that of the SiC fiber reinforced ceramic matrix composite materials without ceramic particle modification in Comparative Example 1. f / Si-YBC composite material, the flexural strength of the SiC particle modified silicon carbide fiber reinforced ceramic matrix composite material prepared in Example 1 is up to 722.3 MPa, which is higher than that of the SiC in Comparative Example 1. f The flexural strength of the composite material with SiC particles in Examples 1-4 is 508.3 MPa, which is 42.1% higher than that of the composite material with SiC particles. 3 N 4 The specific values ​​of the flexural strength of the composite materials obtained in Examples 1-6 and Comparative Example 1 are shown in Table 1 below.

[0050] Table 1 Bending strength of composite materials obtained in Examples 1-6 and Comparative Example 1

[0051] Figure 4 The fracture toughness data of the composite materials prepared in Examples 1-4 are shown in the figure. It can be seen from the figure that among the examples, the fracture toughness of Example 1 is the highest at 23.63 MPa·m 1 / 2 The specific values ​​of the fracture toughness data of the composite materials prepared in Examples 1-4 are shown in Table 2 below.

[0052] Table 2 Fracture toughness of the composite materials obtained in Examples 1-4

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A silicon carbide fiber reinforced ceramic matrix composite material, characterized in that: The invention comprises a silicon carbide fiber reinforcement phase, a boron nitride interface layer and a silicon-based multiphase ceramic matrix from the inside to the outside, wherein the phase composition of the silicon-based multiphase ceramic matrix comprises a phase generated by a melt infiltration reaction, an introduced ceramic particle phase and a silicon-containing binary alloy phase, wherein the alloy element in the silicon-containing binary alloy phase is any one of yttrium, ytterbium, hafnium, molybdenum and aluminum, wherein the phase generated by the melt infiltration reaction comprises a water-oxygen corrosion-resistant phase, a silicon phase, a silicon carbide phase and a boride phase, wherein the water-oxygen corrosion-resistant phase comprises a compound of boron and any one of yttrium, ytterbium, hafnium, molybdenum and aluminum, and wherein the boride phase comprises B 12 (C, Si, B) 3, the particle size of the ceramic particles in the ceramic particle phase is 0.1-10 μm, and the flexural strength of the silicon carbide fiber reinforced ceramic matrix composite material is ≥600 MPa and the fracture toughness is ≥19 MPa·m 1 / 2 .

2. The silicon carbide fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The ceramic particles are selected from at least one of carbide ceramic particles, nitride ceramic particles and boride ceramic particles.

3. The silicon carbide fiber reinforced ceramic matrix composite material according to claim 2, characterized in that: The ceramic particles are selected from at least one of silicon carbide ceramic particles, silicon nitride ceramic particles, zirconium carbide ceramic particles, zirconium nitride ceramic particles and zirconium boride ceramic particles.

4. The silicon carbide fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The silicon carbide fiber reinforced ceramic matrix composite material has a flexural strength of ≥700 MPa and a fracture toughness of ≥20 MPa·m 1 / 2 .

5. A method for preparing a silicon carbide fiber reinforced ceramic matrix composite material as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Depositing a boron nitride interface layer on a silicon carbide fiber preform by a chemical vapor infiltration process to obtain a silicon carbide fiber composite preform; S2, using vacuum impregnation and pressure impregnation treatment to impregnate the multiphase ceramic slurry into the silicon carbide fiber composite preform obtained in step S1, repeating the vacuum impregnation and pressure impregnation until the weight of the silicon carbide fiber composite preform increases by 12-15 wt.%, to obtain a composite material preform; the multiphase ceramic slurry contains 0.5-1% by weight of sodium carboxymethyl cellulose, 20-50% of boron carbide, 10-30% of ceramic particles and the balance of deionized water, and the particle size of the ceramic particles is 0.1-10 μm; S3, the composite material preform described in step S2 is subjected to reactive melt infiltration in the infiltration material to obtain a silicon carbide fiber reinforced ceramic matrix composite material.

6. The method for preparing the silicon carbide fiber reinforced ceramic matrix composite material according to claim 5, characterized in that: Step S1: the silicon carbide fiber preform is formed by laminating silicon carbide fiber cloth or weaving silicon carbide fibers; And / or, the deposition conditions of the boron nitride interface layer in step S1 are boron chloride as a boron source, ammonia as a nitrogen source, a deposition temperature of 600-800° C., and a pressure of 5-10 kPa; And / or, the thickness of the boron nitride interface layer is 500-1000 nm.

7. The method for preparing the silicon carbide fiber reinforced ceramic matrix composite material according to claim 5, characterized in that: The process of vacuum impregnation and pressure impregnation in step S2 is to first place the silicon carbide fiber preform obtained in step S1 in a vacuum vessel, evacuate the vacuum vessel until the air pressure is ≤-0.09 MPa, and maintain it for 20-30 min, then immerse the silicon carbide fiber preform in the composite ceramic slurry and maintain it for 20-40 min; then put the composite ceramic slurry together with the silicon carbide fiber preform into a closed container, pressurize it to 0.6-2.0 MPa, maintain it for 20-120 min, and then take it out; And / or, the particle size of the boron carbide in step S2 is 0.1-10 μm; And / or, the preparation process of the composite ceramic slurry in step S2 is to first dissolve the sodium carboxymethyl cellulose in deionized water at a temperature of 60-80°C, and stir evenly to obtain a dispersed solution; then add the boron carbide and the ceramic particles to the dispersed solution to obtain a mixed slurry; and the mixed slurry is ball-milled to obtain a uniformly dispersed composite ceramic slurry.

8. The method for preparing the silicon carbide fiber reinforced ceramic matrix composite material according to claim 7, characterized in that: The ball mill has a rotation speed of 200-300 r / min, a time of 24-36 h, and a size of the corundum ball of 10-30 mm.

9. The method for preparing the silicon carbide fiber reinforced ceramic matrix composite material according to claim 5, characterized in that: The infiltration material in step S3 is selected from at least one of silicon-yttrium alloy, silicon-ytterbium alloy, silicon-hafnium alloy, silicon-molybdenum alloy and silicon-aluminum alloy; And / or, the insulation temperature of the reaction melt infiltration in step S3 is 1200-1500° C. and the insulation time is 30-90 min.

10. Use of the silicon carbide fiber reinforced ceramic matrix composite material according to any one of claims 1 to 4 in the field of aircraft engines, industrial gas turbines or aerospace engines.

Citation Information

Patent Citations

  • Preparation method of B4C modified C / C-SiC brake material

    CN106478125A

  • High-compactness silicon carbide ceramic-based composite material and preparation method thereof

    CN106588060A

  • Method for improving high temperature water / oxygen erosion resistance of SiCf / Si-B-C self-healing ceramic matrix composite material

    CN109836163A

  • Method for preparing SiCf / Si-Y-B-C composite material by combining vacuum impregnation with reactive melt impregnation

    CN114656275A

  • SiC / SiC-SiBYYb composite material and preparation method thereof

    CN115806442A

Cited By

  • Ceramic embedded metal matrix composite and method of manufacture

    CN122605959A

  • Ceramic embedded metal matrix composite and method of manufacture

    CN122605959B